The Equivalents of the Verbs of Activity in the Spanish Translation of “Metai” (“The Seasons”) by Kristijonas Donelaitis - Lisauskaitė, Agnė (Verbum, 2019)
The equivalence of translation has become a concern for many Lithuanian researchers. The term equivalence is described in the monograph “Contrastive Semantics” (2007) by AloyzasGudavičius. LionginasPažūsis (2014) discusses problems that arise from the lack of equivalence at word level. There are many articles on approaches or strategies of equivalence (D. Masaitienė 1996; A. Leonavičienė 2010; L. Černiuvienė 2013). Some scholars choose to examine the strategies applied in the translation of some linguistic items in novels (V. Končius& A. Nausėda 2006; C. Caro Dugo 2010, 2014, 2015, 2016; A. Cerri; I. Janavičienė 2016). However, there is a lack of research that analyses the Spanish translation of the poem “Metai” or a particular linguistic aspect of this Spanish text. Recent years saw several attempts to fill this gap(C. Caro Dugo 2014, 2015, 2016; A. Cerri 2015). The current research aims to examine the equivalents of the verbs of activity (VAs) in the Spanish translation of the poem. The paper focuses only on those VAs that express actions performed by persons. The VAs which denote actions performed by other living beings or forces of nature were excluded. The research covers 52 verses with verbs of activity, selected from the poem, and their equivalents in the translation into Spanish, which are subjected to qualitative content analysis and means ofcomparative methodology. 52 constructions that express the concepts of Work, Damaging, Speakon topic, Motion, Ingestion and Entertainment were selected applying the qualitative content analysis. The Spanish equivalents of these constructions are examined through the comparative methodology. The obtained results indicated that the translator is faithful to the original text. In order to preserve the expressiveness of the poem, the Spanish translation uses an abundance of verbal lexemes. It was noticed that the equivalents of the same meaning or verbs with a more general meaning specified by an additional lexeme or construction were the main strategies adopted in VA translation into Spanish. In one case only was a Lithuanian verb changed into a Spanish noun. Idioms and figurative words were also chosen as a VA translation strategy in several instances. Nonetheless, all of these lexemes, as derivative of verbs or verbal forms, preserve the verbal nature.This workshould be useful tothe semanticists and translators.